Investigation of standard penetration torque testing (SPT-T) to predict pile performance - Komurka, Van; Wagner, Alan; Winter, Charles J. (Wisconsin Highway Research Program, 2005)
Soil/pile set-up is a time-dependant increase in pile capacity. Incorporation of soil/pile set-up in pile design often has considerable economic benefits, resulting from reduction in pile section, length, and/or size of driving equipment. A number of in-situ tests have been developed to measure set-up that can be performed within a subsurface exploration program. One such test, SPT-Torque (SPT-T) test, is considered to offer the most-favorable combination of applicability of results, ease and simplicity of performing the test, and equipment cost. However, instrumentation has not been formally developed for commercial application, research correlating SPT-T test results to measured soil/pile set-up is limited, and no documented research has involved Wisconsin soils. In addition, previous SPT-T research concentrated on performing tests spanning from several hours to several weeks. Considerably shorter time intervals (on the order of one hour or less) will likely be required if the SPT-T test is to be included in a typical exploration program. The primary objective of this research was to perform short-term SPT-T tests and correlate results to long-term measured soil/pile set-up. The results indicate that there does not appear to be any correlation between set-up values from short-term (1 hour or less) SPT-T tests and unit set-up values obtained from long-term restrikes of test pile installation. Negative set-up (relaxation) exhibited in many short-term SPT-T tests followed by positive set-up also contributes skepticism to using this procedure as a tool to estimate set-up. Therefore, short-term SPT-T testing does not appear to be a practical, economical exploration-phase method to predict soil/pile set-up.
105 p.
Keywords: Torque; Soil penetration test; Piles (Supports); Performance; Field tests; Design